Genomics and Cloning - Fritz, Sandy (Mankato, MN Smart Apple Media, 2003)
A discussion of the field of genetics, focusing on the study of the human genome, genetic engineering, and cloning.
Keywords: Genetics; Genetic engineering; Cloning